2018
DOI: 10.18203/2320-1770.ijrcog20180876
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fetal growth restriction in pregnancy in subjects attending in an obstetric clinic of a tertiary care teaching hospital

Abstract: Background: Intrauterine growth restriction (IUGR) is defined as fetal growth less than the normal growth potential of a specific infant because of genetic or environmental factors. Fetal growth restriction or intrauterine growth restriction is one of the leading causes of perinatal mortality and morbidity in newborns. Fetal growth restriction is a complex multifactorial condition resulting from several fetal and maternal disorders. Objective of present study was to find out incidence of IUGR and assessment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…20 Referrals with FGR were 26.8% similar to that in Singh A et al 15 Hypertensive disorders of Pregnancy (24.39%), thyroid dysfunction (21.95%), anaemia (19.51%) and Gestational diabetes (14.63%) were noted in FGR mothers similar to Satyavrathan V et al and Sharma et al 16,21 Motghare DD et al, Bassetty KC and Jamal M et al described gestational hypertension and anaemia as maternal determinants of FGR. 19,20,22 Caesarean delivery was 75.60% and 67% of them were electives in present study similar to Seal A et al 17 with 68% lower segment caesareans and 54% electives. 24% of women delivered vaginally compared to 32% as in Seal A et al 17 Impending Eclampsia, HELLP syndrome and Eclampsia, accounted for 9.75% of terminations.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…20 Referrals with FGR were 26.8% similar to that in Singh A et al 15 Hypertensive disorders of Pregnancy (24.39%), thyroid dysfunction (21.95%), anaemia (19.51%) and Gestational diabetes (14.63%) were noted in FGR mothers similar to Satyavrathan V et al and Sharma et al 16,21 Motghare DD et al, Bassetty KC and Jamal M et al described gestational hypertension and anaemia as maternal determinants of FGR. 19,20,22 Caesarean delivery was 75.60% and 67% of them were electives in present study similar to Seal A et al 17 with 68% lower segment caesareans and 54% electives. 24% of women delivered vaginally compared to 32% as in Seal A et al 17 Impending Eclampsia, HELLP syndrome and Eclampsia, accounted for 9.75% of terminations.…”
Section: Discussionsupporting
confidence: 86%
“…19,20,22 Caesarean delivery was 75.60% and 67% of them were electives in present study similar to Seal A et al 17 with 68% lower segment caesareans and 54% electives. 24% of women delivered vaginally compared to 32% as in Seal A et al 17 Impending Eclampsia, HELLP syndrome and Eclampsia, accounted for 9.75% of terminations. The most common indication for LSCS in Sinha et al was found to be abnormal Doppler findings (23.72%) followed by severe oligohydramnios (22.03%) and fetal distress (18.64 %) which is observed in Raja Rajeswari et al and in present study.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations